Analysis of Community Behavior in Purchasing Hard Drugs Without Prescription at Pharmacy X District Kalidoni City of Palembang in 2025 - Ahmad Dwi Rendika Akbar; Sabda Wahab; Anggy Utama Putri (CV. Q2 Lantera Ilmiah Institut, 2026)
Use drug hard without recipe doctor is problem serious potential​ cause effect side, resistance, up to death. Research This aim For analyze connection knowledge, attitudes, and actions to behavior public in purchase drug hard without recipes in the sub-district area Kalidoni, Palembang City. Research This use design descriptive quantitative and survey analytics, with primary data collection through questionnaire distributed to 63 respondents. Research results show that : Knowledge own connection negative and significant to behavior society (t = 2.268; p = 0.023), meaning the more tall knowledge, the more low trend purchase drug hard without Recipe; Attitude also plays a role negative and significant (t = 2.759; p = 0.006), indicating attitude positive can lower practice purchase without recipe; Community action influential positive and significant (t = 2.874; p = 0.004), meaning the more often action self-medication done, the more tall trend purchase drug hard without recipe. Research This confirm importance education to community and supervision strict from pharmacies and services health For pressing the culprit use drug hard without recipe. Further study recommended For reach more areas wide as well as dig internal factors in the pharmacy that influence sale drug hard without recipe.